REFORMASI BIROKRASI PEMERINTAHAN MENUJU GOOD GOVERNANCE DALAM PERSPEKTIF ADMINISTRASI PUBLIK - Gedeona, Hendrikus Triwibawanto (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2010)
The concept of managing a good governmental bureaucracy for achieving good governance is not a new thing in Indonesia. Many scholars have analyzed and found determinant factors from different disciplines to generate bureaucratic changes. Thisarticle tries to investigate bureaucratic changes towards good governance from public administration science (a shift of paradigm). The shift of paradigm is then associated to the practical conditions in which corruption cases have been flourishing these days. This elaboration is aimed at developing bureaucratic capacity as one important element of governance, that is to create a goodgovernance.